Impact of salinity and connate water on low salinity water injection in secondary and tertiary stages for enhanced oil recovery in carbonate oil reservoirs. (18th April 2018) - Mohammadkhani, Samira; Shahverdi, Hamidreza; Esfahany, Mohsen Nasr
Abstract: Connate water saturation and its composition, as well as the salinity of injected water, have significant impact on the performance of low salinity water injection (LSWI). Due to the lack of experimental data and difficulties in performing experiments on carbonate rocks, the mechanisms and impact of pertinent parameters involved in the low salinity water flooding in carbonate oil reservoirs is not well understood. In this study, several core flood experiments were conducted on tight carbonate rocks under highly controlled conditions, and using seawater at various dilution ratios as the injected and connate water. The cores were initially established with different connate waters, in terms of saturation and salinity, and the injection scenarios were carried out under secondary and tertiary stages at various salinities. Oil recovery as well as composition and pH of effluent brine were measured to investigate the impact of connate water and salinity on LSWI. The results depicted that oil recovery in the secondary injection stage is maximum for the highest connate water saturation and lowest connate water salinity. Hence, both the salinity of the injected brine and the salinity and saturation of connate brine play a significant role in the performance of LSWI in carbonate rocks. In the tertiary scenario, the highest oil recovery was obtained while both the saturation and salinity of the connate water were minimal. A new mechanism regarding ion exchange and wettability alteration processes was proposed based on ion tracking analysis.